Investigating Endocytic Pathways to the Endoplasmic Reticulum and to the Cytosol Using SNAP‐Trap. (12th November 2012) - Geiger, Roger; Luisoni, Stefania; Johnsson, Kai; Greber, Urs F.; Helenius, Ari
Abstract : Cholera toxin enters cells via an unusual pathway that involves trafficking through endosomes to the endoplasmic reticulum (ER). Whether the toxin induces its own pathway or travels along a physiological retrograde route is not known. To study its trafficking, we labeled cholera toxin B (CTB) or endogenous plasma membrane proteins with a small chemical compound, benzylguanine, which covalently reacts with the protein SNAP‐tag. Using ER‐targeted SNAP‐tag as reporter, we found that transport of CTB to the ER depends on dynamin‐2 and syntaxin 5. Plasma membrane proteins and a fluid‐phase marker added to the medium were also transported to the ER. This flux was not affected by exposing cells to CTB but was inhibited by depleting syntaxin 5 and increased by depleting dynamin‐2. As a control for confined intracellular localization of ER‐targeted SNAP‐tag we used adenovirus‐5, which traffics to endosomes and then escapes into the cytosol. The virus did not react with ER‐targeted SNAP but with cytosolic SNAP. Together, our results establish a new method (SNAP‐trap) to study trafficking of different cargo to the ER and the cytosol and provide evidence for the existence of a constitutive pathway from the cell surface to the ER .